Bacteriocins and bacteriocin producers present in kefir and kefir grains - Powell, Jillian Elizabeth (Stellenbosch : University of Stellenbosch, 2006)
Thesis (Msc Food Sc (Food Science))--University of Stellenbosch, 2006.